If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -4 + -6(x + 4) = 0 Reorder the terms: 3x + -4 + -6(4 + x) = 0 3x + -4 + (4 * -6 + x * -6) = 0 3x + -4 + (-24 + -6x) = 0 Reorder the terms: -4 + -24 + 3x + -6x = 0 Combine like terms: -4 + -24 = -28 -28 + 3x + -6x = 0 Combine like terms: 3x + -6x = -3x -28 + -3x = 0 Solving -28 + -3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '28' to each side of the equation. -28 + 28 + -3x = 0 + 28 Combine like terms: -28 + 28 = 0 0 + -3x = 0 + 28 -3x = 0 + 28 Combine like terms: 0 + 28 = 28 -3x = 28 Divide each side by '-3'. x = -9.333333333 Simplifying x = -9.333333333
| (X+2)(X)=144 | | -22+(-7)= | | 18x^3+48x^2-12x^2=0 | | X=32500-23280 | | 16(n-2)-(n+3)=10 | | f(6)=7x-15 | | 9x^2+6x-10=0 | | 20s+6=5 | | 3(4x-9)=5(3x-5) | | 32x^2-162=0 | | 11+6x-15-4x=2 | | -2.5-32.7=74.1 | | y=ln(4x-8) | | -12=-2k+-4k | | 2x^2+7=-23 | | -12=-2 | | 5x+55=2x+100 | | 6y+4=2x-1 | | y=-5x^2+20t+0.8 | | 7+13= | | 12x+7=8x+15 | | 3(9+7d)=-16 | | 1-cosx-cosx+cos^2x= | | 3(4x+6)=-37+19 | | -30r=-5r+6r | | =(5x^2y^3)(-x^5y)(-2x^4y) | | 10x+7=3x+21 | | 12x-11y=88 | | 5(x-3)=3-4x | | 2(6n+5)+8n=170 | | 3r^3+12r^2+12r=0 | | 5x+3(3x+9)=111 |